Investigation of Sex Education and its Impact on the Sexual Behaviour of Adolescents in Secondary Schools in Benin City, Nigeria. - Aikabeli Priscilla O; Ehimhen Prayer O; Aikpitanyi Maureen (International Journal of Educational Excellence and Innovation, 2025)
Sex education plays a crucial role in shaping the sexual behaviour of adolescents, yet its impact remains a topic of debate. This study was undertaken to investigate sex education and its impact on adolescent sexual behaviour insecondary school in Benin City. To achieve this objective, four research questions and four hypotheses were raised and tested.The design was a questionnaire survey. The population comprised of eighty-four adolescent students of Norman Edward Education Centre, a secondary school in Benin City. The research instrument was a structured questionnaire. Data was analysed using SPSS version 21. Analysis of data revealed asignificant relationship between sex education and the sexual behaviour of adolescents in secondary school in Benin City, high level of awareness and acceptance of sex education among adolescent students, variations in understanding and attitude based on gender, age and educational level and identified key areas where sex education programme could be improved to better address the needs of adolescents. The following recommendations were made. The implementation of properly guided sex education that caters to the diverse needs of students, irrespective of gender or religious beliefs. Active involvement of religious organisations in promoting messages of appropriate sexual conduct and providing accurate information during sermons and religious gatherings to reduce unhealthy sexual behaviour and teenage pregnancies. Establishment of anonymous organisations within schools to provide a safe space for students to seek confidential guidance and support regarding sexual health matters as they may feel uncomfortable discussing such matters with parents or teachers. Introduction of sex education in the pre-adolescent stage to ensure that young people are equipped with essential knowledge and skills regarding sexual health before entering adolescence to help them make informed decisions about their sexual behaviour.